2019
DOI: 10.1038/s41467-019-11714-8
|View full text |Cite|
|
Sign up to set email alerts
|

Cognitive control of complex motor behavior in marmoset monkeys

Abstract: Marmosets have attracted significant interest in the life sciences. Similarities with human brain anatomy and physiology, such as the granular frontal cortex, as well as the development of transgenic lines and potential for transferring rodent neuroscientific techniques to small primates make them a promising neurodegenerative and neuropsychiatric model system. However, whether marmosets can exhibit complex motor tasks in highly controlled experimental designs—one of the prerequisites for investigating higher-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…The monkeys’ hand movements easily suffice these criteria for volition. In addition, the current and other recent behavioral studies showed that monkeys can also produce vocalizations volitionally, albeit only with considerable cognitive effort ( Hage et al, 2013 ; Hage et al, 2016 ; Pomberger et al, 2019 ). At a neuronal level, the current comparison of cued versus spontaneous vocalizations and hand movements showed impressive and highly significant activity differences; neuronal activity in the frontal lobe remains at baseline level for the monkeys’ spontaneous and non-goal directed vocalizations and hand movements but is strongly modulated for volitional and goal-directed responses.…”
Section: Discussionsupporting
confidence: 51%
“…The monkeys’ hand movements easily suffice these criteria for volition. In addition, the current and other recent behavioral studies showed that monkeys can also produce vocalizations volitionally, albeit only with considerable cognitive effort ( Hage et al, 2013 ; Hage et al, 2016 ; Pomberger et al, 2019 ). At a neuronal level, the current comparison of cued versus spontaneous vocalizations and hand movements showed impressive and highly significant activity differences; neuronal activity in the frontal lobe remains at baseline level for the monkeys’ spontaneous and non-goal directed vocalizations and hand movements but is strongly modulated for volitional and goal-directed responses.…”
Section: Discussionsupporting
confidence: 51%
“…This suggests that marmosets are not simply calling more but are specifically producing more calls within the context of active conversations. Third, interactive effects revealed by the model suggests that optimizing communication in these challenging acoustic and social landscapes necessitates a dynamic strategy, one in which marmosets must exert control over both the call structure and the behavior Miller et al, 2009a;Pomberger et al, 2019;Zhao et al, 2019). Consistent with previous experiments (Roy et al, 2011) and results in Experiment 1, the predictability of the scene played a significant role in how marmosets solve the CPP for effective communication.…”
Section: Discussionmentioning
confidence: 99%
“…Results from a Linear Model indicated that these primates did not solely rely on audition to effectively communicate in cocktail parties, but adaptively change their behavior in response to the dynamics of the acoustic scene 44, 45, 46, 47, 48 . To control for acoustic interference, it was necessary to decrease the inter-call interval (ICI) between phees in the Distractor VM conversations which resulted in a systematic change in the periodicity of the Distractor VM conversation (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have mapped the afferent connections of the primary motor, dorsal and ventral premotor areas in this species (Burman et al 2014a, b, 2015), but there have been no studies of the putative premotor areas located near the dorsal midline. Given the rapidly developing use of marmosets in studies of motor control (Bakola et al 2015; Roy et al 2016; Tia et al 2017; Walker et al 2017; Ebina et al 2018, 2019; Pomberger et al 2019), improved knowledge of the pattern of interconnections between cortical areas is likely to lead to better models to understand the mechanistic basis of neuronal interactions leading to the planning and execution of movement, as well as the circuit basis of differences in motor behavior.…”
Section: Introductionmentioning
confidence: 99%